Characterisation of GaN films grown on sapphire by low-temperature cyclic pulsed laser deposition/nitrogen rf plasma - Sanguino, P.
GaN thin films grown by cyclic pulsed laser deposition were characterised by X-ray diffraction (XRD), photoluminescence (PL), and atomic force microscopy. Films were grown on pre-nitridated c-plane sapphire at two substrate temperatures (600 and 650 °C). Films deposited at 650 °C exhibit a higher growth rate which is reflected in the XRD intensity along the GaN (0002) direction. At this substrate temperature, the quality of the PL spectrum was the best. The typical yellow luminescence, YL (2.2 eV) was dominant at the lower deposition temperature. For this substrate temperature change, the near band edge emission (NBE) to YL ratio increased from 0.3 to a value of 17. This NBE emission was peaked at 3.47 eV with a FWHM of 200 meV at 14 K. Optimisation of deposition parameters is suggested to further improve the quality of binary films.